Strategi Pemerintah Kota Bogor Dalam Penerapan SIPD - Tunggal Agung, Catrina Ratu; Kolopaking, Lala M; Harianto, Harianto (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 1 (2022): Jurnal Manajemen Agribisnis, 2022)
Utilization / use of data innovation in the scope of government is the answer with the aim of accelerating development in the region. For this reason, the focus of the government, especially the central government, namely the Directorate General of Regional Development of the Ministry of Home Affairs, takes an approach to the utilization of SIPD, namely the local government information system to be implemented in all regions or regions of the Province, Regency, City in a work to synchronize programs and activities that are being developed in preparation. This research plans to examine the level of readiness (readiness) for the implementation of SIPD, the feasibility of implementing the SIPD data framework and the capabilities of human resources within the Bogor City Government as users of SIPD and then formulate the strategy of the Bogor City Government in implementing SIPD. The information used is primary and secondary data. Primary data was obtained through meetings and polls using the Partial Least Square (PLS) analysis method using smartpls 3.3.3. while secondary data is generated through scientific writing and related reports. This review uses a measurement scale and a SWOT examination. The SWOT investigation is shown from the research results which show that the SWOT investigation distinguishes internal and external elements so that the results are 4 Strengths, 5 Weaknesses, 3 Opportunities and 4 Threats. The highest weight in the definition of the procedure, namely the Weakness-Opportunity (WO) methodology, is to increase the readiness of regional apparatus, provide information technology infrastructure facilities, an adequate number of human resources, especially placing human resources for clients of information system data frameworks with an innovation-based learning foundation.